Konstrukcja prawna subwencji ogólnej w polskich regulacjach prawnych dochodów jednostek samorządu terytorialnego - Pest, Przemysław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The objective of the monograph is to present and explore the evolution of the legal construction of the general subsidy in Polish regulations governing the revenues of local self-government units. This goal will be achieved through a dogmatic legal and historico-legal analysis focussed primarily on the provisions of successive acts regulating the issue of revenues of local self-government units since 1991, and supplemented by examination of other laws, such as the acts on self-government and on public finances. The author’s primary intent was to show that the essence of the general subsidy in the system of revenues of local self-government units is the performance of a balancing function, consisting in enhancing the own revenues of local self-government units, facilitating the performance of own tasks at the level of minimum standards by those units in each part of the country. The balancing function is considered necessary due to: 1) the differences in revenue generation potential and/or inequalities in the spending needs of local self-government units, and 2) the necessity of ensuring that local self-government units are financially equipped to perform own tasks. The monograph is comprised of five chapters. The first, an introduction to the research performed, takes as its subject analysis of the notion of the general subsidy, the model applied in its calculation, its functions, and key aspects necessary for understanding the legal construction of the general subsidy: the method in which it is financed, the model employed for its calculation, the criterion for the division of the general subvention among local self-government units, and objectivization of the general subvention. Chapters 2 through 5 present and explore a range of acts governing the issue of revenues of local self-government units, with subchapters detailing particular aspects of the general subsidy.
Keywords: general subsidy; local self-government; commune; county; province; Robin Hood transfers; balancing function; transfers; Polish Constitution; objectivization; criteria for division; revenue potential; compensatory function; parity of subsidy; tax revenues; Constitutional Tribunal; subjective right; budget; financing of tasks; method of financing; model of calculation